A review of the nursing role in central venous cannulation: implications for practice policy and research - Alexandrou, Evan; Spencer, T.; Frost, S.; Parr, M.; Davidson, Patricia; Hillman, K. (Blackwell Publishing, 2009)
Aims and objectives. The aim of this article is to review published studies about central vein cannulation to identify implications for policy, practice and research in an advanced practice nursing role.Design. Modified integrative literature review.Methods. Searches of the electronic databases: Cumulative Index of Nursing and Allied Health Literature (CINAHL); Medline, Embase, and the World Wide Web were undertaken using MeSH key words. Hand searching for relevant articles was also undertaken. All studies relating to the nurses role inserting central venous cannulae in adult populations met the search criteria and were reviewed by three authors using a critical appraisal tool.Results. Ten studies met the inclusion criteria for the review, all reported data were from the UK. There were disparate models of service delivery and study populations and the studies were predominantly non experimental in design. The results of this review need to be considered within the methodological caveats associated with this approach. The studies identified did not demonstrate differences in rates of adverse events between a specialist nurse and a medical officer.Conclusions. There were only a small number of studies found in the literature review and the limited availability of clinical outcome data precluded formal analysis from being generated.Relevance to clinical practice. Central vein cannulation is potentially an emerging practice area with important considerations for policy practice and research. Training specialist nurses to provide such a service may facilitate standardising of practice and improving surveillance of lines, and possibly improve the training and accreditation process for CVC insertions for junior medical officers. For this to occur, there is a need to undertake well-conducted clinical studies to clearly document the value and efficacy of this advanced practice nursing role.